A Comparative Biology of Microglia Across Species - Sharma, Kaushik; Bisht, Kanchan; Eyo, Ukpong B. (Frontiers in Cell and Developmental Biology, 2021)
Microglia are unique brain-resident, myeloid cells. They have received growing interest for their implication in an increasing number of neurodevelopmental, acute injury, and neurodegenerative disorders of the central nervous system (CNS). Fate-mapping studies establish microglial ontogeny from the periphery during development, while recent transcriptomic studies highlight microglial identity as distinct from other CNS cells and peripheral myeloid cells. This evidence for a unique microglial ontogeny and identity raises questions regarding the significance of their emergence in evolution where less research has been conducted. This review will examine the available evidence for microglia in invertebrate and vertebrate species to understand the significance of microglial emergence in evolution. Further, we discuss similarities and differences in microglial identity, ontogeny, and physiology across species. This discussion highlights conserved and divergent microglial properties through evolution. Finally, we suggest several interesting research directions from an evolutionary perspective to adequately understand the significance of microglia emergence. A proper appreciation of microglia from this evolutionary perspective could inform the development of specific therapies geared at targeting microglia in various pathologies.